Electrochemical intercalation of fullerene and hydrofullerene with sodium. (April 2018) - Scaravonati, S.; Magnani, G.; Gaboardi, M.; Allodi, G.; Riccò, M.; Pontiroli, D.
Abstract: We herein report on the ability of fullerene C60 and hydrogenated fullerene C60 Hx (x∼39) to operate as negative electrodes in novel Na-ion batteries. Building upon the known solubility of C60 in common organic electrolytes used in batteries, we developed a suitably optimized solid-state Na-(polyethylene oxide) electrolyte for this application. Electrochemical and structural properties of the fullerene electrodes were investigated through cyclic voltammetry, fixed-current charge/discharge of the electrodes, impedance spectroscopy and powder X-ray diffraction. Both C60 and hydrogenated C60 have been electrochemically intercalated with sodium. Specific capacities after the first cycle are 250 mAh g −1 and 230 mAh g −1 for C60 and C60 Hx respectively. However, C60 electrode shows a strong irreversible character after the first discharge, probably due to the formation of stable polymeric Nax C60 phases, where Na + ions diffusion is hindered. On the contrary, C60 Hx displays better reversibility, suggesting that hydrogenation of the buckyball could be effective to preserve sufficiently large interstitial pathways for Na + diffusion upon intercalation. Graphical abstract: Image 1